Energy saving and energy efficiency policies in the European union - S. T. Kasyuk (Известия высших учебных заведений: Проблемы энергетики, 2017)
This article analyses energy saving and energy efficiency policies in the European Union. Directives EU in this area since 1993 are described. The basic provisions of the Directive 2012/27 on energy efficiency and Energy Efficiency Plan 2011 are analyzed. The problem of the implementation of EU policy in this area with the framework of the open method of coordination is described.